De novo assembly and characterization of leaf and floral transcriptomes of the hybridizing bromeliad species (Pitcairnia spp.) adapted to Neotropical Inselbergs. (2nd March 2016) - Palma‐Silva, C.; Ferro, M.; Bacci, M.; Turchetto‐Zolet, A. C.
Abstract: We present the leaf and floral transcriptomes of two hybridizing bromeliad species that differ in their major pollinator systems. Here we identified candidate genes responsible for pollinator attraction and reproductive isolation in these two species. We searched for candidate genes involved in floral traits, such as colour. Approximately 34 Gbp of cDNA sequence data were produced from both tissues and species, resulting in a total of 424 506 914 raw reads. The de novo‐assembled transcriptomes consisted of a total of 263 955 contigs, further clustered into 110 977 unigenes. Over 58% of the unigenes were functionally annotated and assigned to one or more Gene Ontology terms. The transcriptomes revealed 144 unique transcripts that encode key enzymes in the flavonoid and anthocyanin biosynthesis pathways. The domain/family annotation and phylogenetic analysis allowed us to infer, by homology, potential functions of the genes encoding MYB, HD‐ZIP and bZIP‐HY5 transcription factors, as well as WD40 protein, which may be involved in anthocyanin and flavonoid regulation in these species. These candidate genes are associated with natural regulation in flower colour in other plant species and will facilitate future studies aimed at elucidating the molecular basis of adaptive differentiation and the evolution of mechanisms of pollinator‐mediated reproductive isolation in these two bromeliads. In addition, we identified a total of 49 439 microsatellite loci. These resources will assist future research into adaptation and speciation events in bromeliad species, thus providing a starting point for investigation of the molecular mechanisms of the traits responsible for their reproductive isolation.